2018
DOI: 10.1186/s40635-018-0172-7
|View full text |Cite
|
Sign up to set email alerts
|

A high-flow nasal cannula system with relatively low flow effectively washes out CO2 from the anatomical dead space in a sophisticated respiratory model made by a 3D printer

Abstract: BackgroundAlthough clinical studies of the high-flow nasal cannula (HFNC) and its effect on positive end-expiratory pressure (PEEP) have been done, the washout effect has not been well evaluated. Therefore, we made an experimental respiratory model to evaluate the respiratory physiological effect of HFNC.MethodsAn airway model was made by a 3D printer using the craniocervical 3D-CT data of a healthy 32-year-old male. CO2 was infused into four respiratory lung models (normal-lung, open- and closed-mouth models;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
(20 reference statements)
3
26
0
1
Order By: Relevance
“…Analysis of our data, therefore, suggested that the reduction of _ V E observed at 40 and 60 L/min, associated with stable V A (ie, stable capillary P CO 2 ), is the in vivo expression of a reduction in dead-space ventilation related to a major decrease in breathing frequency and a washout of the anatomic dead space. This observation was in line with previous data obtained on the bench with upper-airway models, 26,40 which demonstrated that HFNC was capable of effectively washing out the upper airways and thus reducing CO 2 rebreathing with relatively low flows. As a result of this dead-space washout, HFNC with flow that ranged from 20 to 40 L/min may reduce P CO 2 in the clinical setting, as recently evidenced by Bräunlich et al 19 in stable subjects with COPD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Analysis of our data, therefore, suggested that the reduction of _ V E observed at 40 and 60 L/min, associated with stable V A (ie, stable capillary P CO 2 ), is the in vivo expression of a reduction in dead-space ventilation related to a major decrease in breathing frequency and a washout of the anatomic dead space. This observation was in line with previous data obtained on the bench with upper-airway models, 26,40 which demonstrated that HFNC was capable of effectively washing out the upper airways and thus reducing CO 2 rebreathing with relatively low flows. As a result of this dead-space washout, HFNC with flow that ranged from 20 to 40 L/min may reduce P CO 2 in the clinical setting, as recently evidenced by Bräunlich et al 19 in stable subjects with COPD.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, it has recently been shown that endtidal P CO 2 could be reduced up to 30 mm Hg when applying HFNC at 60 L/min to an experimental model that simulates normal lung with a closed mouth. 40 Such a reduction of P CO 2 , even transient, and, if confirmed in further studies, could explain both the absence of improvement in WOB and the increase in inspiratory resistance (accompanied by an increase in DP es ) observed in our subjects, as previously described by Jounieaux et al 42 in healthy subjects who were undergoing nasal intermittent positive-pressure ventilation. Another explanation for the absence of improvement in respiratory effort with HFNC in this population of healthy subjects was the baseline values, which were already low, in line with what is described in the literature 35,43 and, therefore, subject to minimal improvement despite significant reduction in dead-space ventilation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Conversely, we found that HFNC was inferior to VM in a few patients (Case 6, 7, 9). A recent experimental study using an airway model made with a 3D printer demonstrated that increasing the flow rate of HFNC generates higher positive end-expiratory pressure (PEEP) but does not necessarily increase the washout effects [25]. In our study, two patients complained about nasal pain, although it improved immediately.…”
Section: Discussionmentioning
confidence: 46%
“…In fact, the literature reports reduced anatomic dead space due to increased nasopharyngeal washout, with a consequently larger fraction of minute ventilation participating in gas exchange. 35 Frequently, candidates for liver transplantation display a restricted respiratory pattern related to the size of the ascites and/or pleural effusion. 36 In fact, in our population, we detected a significantly low preoperative P aCO 2 , especially those in the standard O 2 group who had more ascites.…”
Section: Discussionmentioning
confidence: 99%